2019
DOI: 10.33549/physiolres.933949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-OHDA on hypercapnic ventilatory response in the rat model of Parkinson’s disease

Abstract: Breathing impairments, such as an alteration in breathing pattern, dyspnoea, and sleep apnoea, are common health deficits recognised in Parkinson’s disease (PD). The mechanism that underlies these disturbances, however, remains unclear. We investigated the effect of the unilateral damage to the rat nigrostriatal pathway on the central ventilatory response to hypercapnia, evoked by administering 6-hydroxydopamine (6-OHDA) into the right medial forebrain bundle (MFB). The respiratory experiments were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…In other studies, carried out by Andrzejewski and Budzinska, it was observed that animals that received 6-OHDA in the region of the medial forebrain bundle, representing mild cases of PD, presented an increase in VT and a reduction in fR under conditions of hypercapnia and hypoxia, maintaining a VE practically unchanged in the experimental animals (129,130). These findings in animal models reinforce the results found in patients with PD by Seccombe.…”
Section: Central Respiratory Disorderssupporting
confidence: 82%
“…In other studies, carried out by Andrzejewski and Budzinska, it was observed that animals that received 6-OHDA in the region of the medial forebrain bundle, representing mild cases of PD, presented an increase in VT and a reduction in fR under conditions of hypercapnia and hypoxia, maintaining a VE practically unchanged in the experimental animals (129,130). These findings in animal models reinforce the results found in patients with PD by Seccombe.…”
Section: Central Respiratory Disorderssupporting
confidence: 82%
“…Other neurotransmitter systems like serotonergic or noradrenergic have been postulated to contribute to respiratory PD abnormalities [8,12,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study performed in 6-OHDA-induced PD model demonstrated decrease in expression of neurokinin 1 receptor in the pre-Bötzinger Complex and phox2b-expressing neurons in retrotrapezoid nucleus corresponding with frequency of breathing decline in normoxic breathing and decreased tachypneic response to hypercapnia [8,10]. Our previous study in unilateral 6-OHDA model displayed increased tidal volume and attenuated respiratory rate responses during hypoxia and hypercapnia in comparison to sham-operated rats [11,12].…”
Section: Introductionmentioning
confidence: 85%
“…These changes in neuromediators concentrations could be responsible for the breathing changes observed in this model. As a possible mechanism of different modulation of phrenic and hypoglossal reactions, the authors suggest the involvement of a modified mechanism of dopamine efflux and of serotonin and orexin during hypoxia (Andrzejewski et al 2019).…”
Section: Lessons Learned From Animal Models Of Pdmentioning
confidence: 97%